Improved DV-Hop Node Localization Algorithm in Wireless Sensor Networks - Xiao Chen; Benliang Zhang (International Journal of Distributed Sensor Networks)
An improved algorithm is put forward to improve the poor locating performance of the DV-Hop algorithm, which is one of the range-free algorithms in wireless sensor networks. Firstly, we set some anchor nodes at the border land of monitoring regions. Secondly, the average one-hop distance between anchor nodes is modified, and the average one-hop distance used by each unknown node for estimating its location is modified through weighting the received average one-hop distances from anchor nodes. Finally, we use the particle swarm optimization to correct the position estimated by the 2D hyperbolic localization algorithm, which makes the result closer to the actual position. The simulation results show that the proposed algorithm has better localization performance in the localization precision and stability than the basic DV-Hop algorithm and some existing improved algorithms.